2016
DOI: 10.1080/21505594.2016.1200215
|View full text |Cite
|
Sign up to set email alerts
|

Dectin-1 is required for miR155 upregulation in murine macrophages in response toCandida albicans

Abstract: The commensal fungal pathogen Candida albicans is a leading cause of lethal systemic infections in immunocompromised patients. One of the main mechanisms of host immune evasion and virulence by this pathogen is the switch from yeast form to hyphal growth morphologies. Micro RNAs (miRNAs), a small regulatory non-coding RNA, has been identified as an important part of the immune response to a wide variety of pathogens. In general, miRNAs act by modulating the intensity of inflammatory responses. miRNAs act by ba… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
13
1
4

Year Published

2017
2017
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 19 publications
(21 citation statements)
references
References 70 publications
0
13
1
4
Order By: Relevance
“…Therefore, it is reasonable to hypothesize that receptor binding on the cell surface may be one of the pathways by which PH-EPS acts on macrophages. To recognize various components on the fungal cell wall, macrophages express PRRs on their surface through which pathogen-associated molecular patterns can be recognized (42). Recent studies have demonstrated that PRRs such as TLR4, TLR2, CR3 and Dectin-1 have significant roles in macrophage activation when being exposed to polysaccharides (14,4345).…”
Section: Resultsmentioning
confidence: 99%
“…Therefore, it is reasonable to hypothesize that receptor binding on the cell surface may be one of the pathways by which PH-EPS acts on macrophages. To recognize various components on the fungal cell wall, macrophages express PRRs on their surface through which pathogen-associated molecular patterns can be recognized (42). Recent studies have demonstrated that PRRs such as TLR4, TLR2, CR3 and Dectin-1 have significant roles in macrophage activation when being exposed to polysaccharides (14,4345).…”
Section: Resultsmentioning
confidence: 99%
“…miR‐155 is known as one of the master regulatory miRNAs in the immunological processes. Agustinho et al revealed that miR‐155 induction by C. albicans hyphae was fully dependent on dectin‐1 which exerted the Syk‐dependent pathway . They also identified reduced mRNA expression of some of the miR‐155 targets, such as MyD88, SHIP‐1, SOCS1 and IKKe that was occurred soon after miR‐155 detection.…”
Section: Mirnas Profiles Following Fungal Exposurementioning
confidence: 99%
“…In a murine model of subchronic A. fumigatus inhalation exposure, Croston et al showed that significantly downregulated miR-29a-3p was predicted to regulate C-type lectin domain family 7 member A, the gene that codes for Dectin-1 ( 91 ). A recent study found that following exposure to C. albicans , Dectin-1 is required for the upregulation of miR-155 in murine macrophages ( 93 ). Along with an increase in miR-30-5p and miR-210-3p in THP-1 cells treated with β-glucan isolated from C. albicans , Du et al found that miR-146a was increased upon Dectin-1 stimulation and negatively regulated the resultant inflammatory response ( 94 ).…”
Section: Fungal Exposure: Role Of Mirnasmentioning
confidence: 99%